2005
DOI: 10.1590/s1517-86922005000400003
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre protocolos diretos e indiretos de avaliação da aptidão aeróbia em indivíduos fisicamente ativos

Abstract: O limiar anaeróbio individual (IAT), o limiar glicêmico individual (IGT), a velocidade associada ao VO2max (Vmax), a velocidade média em corrida de 3.000m (Vm3km) e a velocidade crítica (VC) têm sido utilizados na avaliação aeróbia e prescrição de exercício para atletas-corredores. No entanto, estudos comparando estes parâmetros e sua possível aplicação para indivíduos não atletas ainda não foram realizados. Os objetivos do presente estudo foram comparar e estabelecer as relações entre IAT, IGT, Vmax, Vm3km e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
3
0
2
Order By: Relevance
“…In the present study only two coordinates to calculate CV were used, agreeing with previous studies (de Lucas et al, 2012;Pacheco et al, 2006;Penteado et al, 2014;Silva et al, 2005;Simões et al, 2005). Several studies have shown that two coordinates are enough to determine CV in adult trained runners (de Lucas et al, 2012;Simões et al, 2005), moderately trained adults (Smith, Kendall, Fukuda, Cramer, & Stout, 2011), physically active adults (Pacheco et al, 2006;Silva et al, 2005), adult cyclists (Hiyane et al, 2006) and youth swimmers (Altimari et al, 2007). Housh et al (1990), for instance, submitted 12 young adults to four loads until exhaustion and CP was determined with two, three and four coordinates.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study only two coordinates to calculate CV were used, agreeing with previous studies (de Lucas et al, 2012;Pacheco et al, 2006;Penteado et al, 2014;Silva et al, 2005;Simões et al, 2005). Several studies have shown that two coordinates are enough to determine CV in adult trained runners (de Lucas et al, 2012;Simões et al, 2005), moderately trained adults (Smith, Kendall, Fukuda, Cramer, & Stout, 2011), physically active adults (Pacheco et al, 2006;Silva et al, 2005), adult cyclists (Hiyane et al, 2006) and youth swimmers (Altimari et al, 2007). Housh et al (1990), for instance, submitted 12 young adults to four loads until exhaustion and CP was determined with two, three and four coordinates.…”
Section: Discussionsupporting
confidence: 87%
“…This model does not differ from other models in running (Simões et al, 2005). Only two distances (coordinates) were adopted in order to obtain CV, as previously cited (De Lucas, Dittrich, Junior, de Souza, & Guglielmo, 2012;Pacheco, Silva, Baldissera, Campbell, Liberti, 2006;Penteado et al, 2014;Silva, Pacheco, Campbell, Baldissera, & Simões, 2005;Simões et al, 2005). The distances were chosen with at least a 5min interval between durations (Housh, Housh, & Bauge, 1990) and allowing a total trial time between 3 and 15 min, as recommended (Greco, 2000;Kranenburg & Smith, 1996).…”
Section: Calculating the Critical Velocitymentioning
confidence: 99%
“…This is probably due to the low emphasis given to specific aerobic training. 25 The anaerobic contribution to the global energy demand is emphasized when the frequency of rapid stimuli occurs due to accelerated anaerobic glycolysis. 26,27 This response is evident through the blood lactate levels, which can exceed 12 mmol .…”
Section: ■ Discussionmentioning
confidence: 99%
“…Isso pode ser justificado em função da vVO 2 max representar tanto a participação do metabolismo aeróbio como do anaeróbio o que 694 poderia explicar a maior relação com a performance de provas de média distância (1,5 km e 3 km), visto que 16 % da energia utilizada durante o exercício realizado na vVO 2 max é derivada do metabolismo anaeróbio (FAINA et al, 1997 max com corredores moderadamente treinados, verificando que houve correlação dessa variável com a distância tanto no pré (r = -0,76) quanto no pós treinamento (r = -0,81). Mesmo para indivíduos ativos é possível obter uma boa predição de performance por meio da vVO 2 max com a distância de 3 km (r = 0,91), que pode ser constatado no estudo realizado por Silva et al (2005). Por outro lado, Lacour et al (1990), além de verificarem correlação da vVO 2 max com a velocidade média de 1,5 km (r = 0,62) e 3 km (r = 0,64), também observaram correlação com a performance de 5 km (r = 0,86).…”
Section: Discussionunclassified